2018
DOI: 10.1093/nar/gky723
|View full text |Cite
|
Sign up to set email alerts
|

p15PAF binding to PCNA modulates the DNA sliding surface

Abstract: Abstractp15PAF is an oncogenic intrinsically disordered protein that regulates DNA replication and lesion bypass by interacting with the human sliding clamp PCNA. In the absence of DNA, p15PAF traverses the PCNA ring via an extended PIP-box that contacts the sliding surface. Here, we probed the atomic-scale structure of p15PAF–PCNA–DNA ternary complexes. Crystallography and MD simulations show that, when p15PAF occupies two subunits of the PCNA homotrimer, DNA within the ring channel binds the unoccupied subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 57 publications
(111 reference statements)
0
28
0
1
Order By: Relevance
“…We found that both the interaction with PCNA and dual mono-ubiquitylation by UHRF1 are essential for PAF15 function in the maintenance of DNA methylation. PAF15 is an intrinsically disordered protein and binds to trimeric PCNA via the PIPbox motif at the front face and its N-terminus interacts with the inner ring of PCNA and exits the clamp from the back face 48 , suggesting that the ubiquitylation sites of PAF15 could locate near the nascent strand where a methyl group does not yet exist. Thus, PAF15Ub2 could directly recruit DNMT1 to the back face of PCNA, facilitating the processivity of DNMT1-mediated DNA methylation on the nascent DNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We found that both the interaction with PCNA and dual mono-ubiquitylation by UHRF1 are essential for PAF15 function in the maintenance of DNA methylation. PAF15 is an intrinsically disordered protein and binds to trimeric PCNA via the PIPbox motif at the front face and its N-terminus interacts with the inner ring of PCNA and exits the clamp from the back face 48 , suggesting that the ubiquitylation sites of PAF15 could locate near the nascent strand where a methyl group does not yet exist. Thus, PAF15Ub2 could directly recruit DNMT1 to the back face of PCNA, facilitating the processivity of DNMT1-mediated DNA methylation on the nascent DNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA cannot spontaneously assemble around DNA and must first be loaded over primer–template junctions by the replication factor C (RFC) complex in an ATP‐dependent fashion . The PCNA–DNA interaction is mediated (at two of three surfaces) by the peptidic arms of PCNA‐associated factor p15 PAF , which reach into the clamp barrel from protein bound at the PIP‐box, thereby fastening DNA within the PCNA ring …”
Section: Pcna Structure and Functionmentioning
confidence: 99%
“…Some of these interactions require PCNA to be DNA‐bound, whereas others rely on post‐translationally modified PCNA to enhance recognition or binding affinity . For example the translesion DNA synthesis (TLS) polymerases preferentially bind mono‐ubiquitylated PCNA . There is not believed to be a cancer‐related mutant, despite the clear link between PCNA and cancerous cells …”
Section: Pcna Structure and Functionmentioning
confidence: 99%
“…KIAA0101 is a cell-cycle regulated oncoprotein that regulates DNA synthesis, maintenance of DNA methylation, and DNA-damage bypass, through the interaction with the human sliding clamp PCNA [3,[6][7][8][9][10][11][12][13][14]. KIAA0101 is part of a DNA-replication complex with PCNA, DNA polymerase delta (DNA Pol δ), and the endonuclease Fen-1 in the replication foci [6].…”
Section: Introductionmentioning
confidence: 99%
“…Then, KIAA0101 protein levels drop rapidly at the mitotic exit (late M and G1 phases) via polyubiquitination mediated by the anaphase-promoting complex/cyclosome (APC/C) complex, a cell cycle-regulated E3 ubiquitin ligase, leading to its degradation by the proteasome [8]. The depletion of KIAA0101 signi cantly decreases DNA synthesis [6][7][8][9], indicating that KIAA0101 modulates the function of PCNA as a processivity factor [10,11]. KIAA0101 is an intrinsically disordered protein that binds via its central PIP-box to the front-face of PCNA and its N-terminus interacts with the inner ring of PCNA and pass through the PCNA from the back-face [10,11].…”
Section: Introductionmentioning
confidence: 99%